2015
DOI: 10.1088/0004-637x/810/1/51
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation of Supermassive Black Holes in Metal-Enriched Gas at the Heart of High-Redshift Galaxy Mergers

Abstract: We present novel 3D multi-scale SPH simulations of gas-rich galaxy mergers between the most massive galaxies at z ∼ 8 − 10, designed to scrutinize the direct collapse formation scenario for massive black hole seeds proposed in Mayer et al. (2010). The simulations achieve a resolution of 0.1 pc, and include both metallicity-dependent optically-thin cooling and a model for thermal balance at high optical depth. We consider different formulations of the SPH hydrodynamical equations, including thermal and metal di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 110 publications
9
131
0
Order By: Relevance
“…This may suggest that halos experiencing major mergers in their recent past may form supermassive stars more easily, for lower strengths of UV field, while perhaps this is not happening in haloes formed via minor mergers and accretion. In fact, Mayer et al (2014) suggested that the merging of very massive galactic cores, > 10 9 M ⊙ , may form a stable nuclear disk with very large gas inflow rates. They argue that merging of such systems leads to the enhanced inflow rates and helps in the formation of a massive black hole.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that halos experiencing major mergers in their recent past may form supermassive stars more easily, for lower strengths of UV field, while perhaps this is not happening in haloes formed via minor mergers and accretion. In fact, Mayer et al (2014) suggested that the merging of very massive galactic cores, > 10 9 M ⊙ , may form a stable nuclear disk with very large gas inflow rates. They argue that merging of such systems leads to the enhanced inflow rates and helps in the formation of a massive black hole.…”
Section: Discussionmentioning
confidence: 99%
“…When the two protogalaxies merge, merger-driven inflows of metal-enriched gas produce a massive (≥ 10 9 M ) compact nuclear gas disk with a high angular momentum. In the inner parsecs an ultra-dense massive disky core is formed, which can turn into a supermassive star and collapse directly into a SMBH of 10 8 -10 9 M (Mayer et al 2015). Although this avenue of SMBH formation requires initial conditions more complex than those of the direct collapse in less massive halos scenario, it offers an explanation for the existence of high-z SMBHs without having to prevent gas cooling and star formation nor requiring primordial gas composition.…”
Section: Introductionmentioning
confidence: 99%
“…While the nature of the initial conditions in this scenario is more complex than those based on the collapse of primordial gas in less massive DM halos, and may involve complications such as the pre-existence of BHs in the centers of the merging galaxies, somewhat idealized simulations suggest that heavy, optically thick accretion flows may well lead to the formation of such massive central objects (Mayer et al 2015; but see also Ferrara et al 2013). …”
Section: Expected Mass Scale Of Black Hole Progenitorsmentioning
confidence: 99%